Functional diversity of macrozoobenthos under adverse oxygen conditions in the southern Baltic Sea - Halina Kendzierska; Urszula Janas (Scientific Reports, 2024)
Abstract Oxygen deficiency is a major problem in the Baltic Sea. To study the impact of hypoxia on the functional diversity of benthic fauna and the possibility of macrozoobenthos recovery, data were analyzed in a gradient of oxygen conditions in the Gdańsk Basin. The research conducted on the basis of biological traits analysis enabled us to analyze the number, type and spatial distribution of biological traits—a proxy for functions performed by macrozoobenthos. A significant depletion of macrofauna was already observed under conditions of reduced oxygen above the bottom, both in terms of functional diversity and biomass. Although taxa observed in hypoxia (DO < 2 mL L−1) perform a number of functions, the remaining species do not form complex structures in the sediments or cause deep bioturbation and bioirrigation. Moreover, their extremely low biomass plays an irrelevant role in benthic–pelagic coupling. Thus, benthic fauna under hypoxia is not an element that ensures the functioning of the ecosystem. We assess that traits important for species dispersal and the presence of taxa resistant to short-term hypoxia in the oxic zone above the halocline provide a “backup” for ecosystem functioning under altered diverse oxygen conditions below the halocline after cessation of hypoxia in the southern Baltic Sea.